Sustainable Design and Manufacturing 2018 : proceedings of the 5th International Conference on Sustainable Design and Manufacturing (KES-SDM-18) /: proceedings of the 5th International Conference on Sustainable Design and Manufacturing (KES-SDM-18). ([2019]) - Unknown
No abstract available